Transnational, translocal, and transient: Economic communities of Arab entrepreneurs in Yiwu, China. Issue 5 (5th December 2021) - Yang, Xin; Wang, Qingfang
Abstract: Despite an accumulation of literature on ethnic, immigrant, and transnational entrepreneurship, we still know very little about transnational entrepreneurship among less‐developed countries especially when culture and religion are concerned. Based on long‐term ethnographic work in immigrant Arab communities, this study examines the economic communities of transnational Arab entrepreneurs in Yiwu, a global wholesale hub city in China. We find that the motivation of profit‐seeking and transitional chain migration set the premise and foundation for Arab immigrant communities. The transnational networks of kinship and geo‐relationship are further integrated with Arab entrepreneurs' translocal networks based on religion, culture, profession, and educational experiences in shaping the economic activities of Arab entrepreneurs. At the same time, taking profit‐seeking as the primary goal instead of evident political and religious pursuits, their experiences also feature with transiency under the current institutional constraints. This study provides different evidence of transnational mixed embeddedness of immigrant ethnic entrepreneurship from a less‐developed economy where the state has a dominant role in economic, cultural, and political control.